Altered gene expression signature of early stages of the germ line supports the pre‐meiotic origin of human spermatogenic failure. (7th May 2014) - Bonache, S.; Algaba, F.; Franco, E.; Bassas, L.; Larriba, S.
Summary The molecular basis of spermatogenic failure (SpF) is still largely unknown. Accumulating evidence suggests that a series of specific events such as meiosis, are determined at the early stage of spermatogenesis. This study aims to assess the expression profile of pre‐meiotic genes of infertile testicular biopsies that might help to define the molecular phenotype associated with human deficiency of sperm production. An accurate quantification of testicular mRNA levels of genes expressed in spermatogonia was carried out by RT‐qPCR in individuals showing SpF owing to germ cell maturation defects, Sertoli cell‐only syndrome or conserved spermatogenesis. In addition, the gene expression profile of SpF was compared with that of testicular tumour, which is considered to be a severe developmental disease of germ cell differentiation. Protein expression from selected genes was evaluated by immunohistochemistry. Our results indicate that SpF is accompanied by differences in expression of certain genes associated with spermatogonia in the absence of any apparent morphological and/or numerical change in this specific cell type. In SpF testicular samples, we observed down‐regulation of genes involved in cell cycle (CCNE1 and POLD1), transcription and post‐transcription regulation (DAZL, RBM15 and DICER1), protein degradation (FBXO32 and TM9SF2) and homologous recombination in meiosis (MRE11A and RAD50) which suggests that the expression of these genes is critical for a proper germ cell development. Interestingly, a decrease in the CCNE1, DAZL, RBM15 and STRA8 cellular transcript levels was also observed, suggesting that the gene expression capacity of spermatogonia is altered in SpF contributing to an unsuccessful sperm production. Altogether, these data point to the spermatogenic derangement being already determined at, or arising in, the initial stages of the germ line.